Kazakhstan’s Сhairmanship of the OIC: the History and prospects - Saktaganova, Z.G.; Suinova, A.S. (Ye.A.Buketov Karaganda State University Publishing house, 2011)
In article the history of origin and development of idea of «Pan-Islamism» on territories of Saudi Arabia and its distribution for country limits reveals and all over the world. Authors investigate attempts of the Arabian states to extend idea of association on the basis of Islamic solidarity through the international organizations. One of such effective associations for today is the Organization of «Islamic conference». In article preventive acts and settlement of organization in the Middle East conflicts, the place and role of Organization of «Islamic conference» in international relations and possible prospects of Chairmanship of the Republic of Kazakhstan in the Meeting of Ministers of Foreign Affairs of the Organization of «Islamic conference» in 2011 are analyzed.
Қазақстанның Ынтымақтастық Ислам Ұйымына төрағалық етуі: тарихы мен болашағы
Председательствование Казахстана в ОИК: история и перспективы
Keywords: Kazakhstan; Republic of Kazakhstan; Saudi Arabia; Arabian states; Middle East; Islamic conference; society; dynamics; development; historical